Plutarch's Lives, Volume 1 (of 4) - Plutarch, 46-120?; Long, George, 1800-1879; Stewart, Aubrey, 1844-1918 (Salt Lake City, UT : Project Gutenberg, 2004)
"Plutarch's Lives, Volume 1 (of 4)" by Plutarch is a series of biographies written in Greek probably at the beginning of the second century. This monumental work pairs the lives of famous Greeks and Romans to reveal their shared moral virtues and failings. Through 23 paired biographies$1 (Bmatching figures like Alexander the Great with Julius Caesar$1 (BPlutarch explores how character shapes destiny. Rather than pure history, these literary portraits examine the psychological and moral motivations behind greatness, encouraging readers to reflect on virtue, vice, and human nature itself. (This is an automatically generated summary.)s
Life of Plutarch -- Life of Theseus -- Life of Romulus -- Comparison of Theseus and Romulus -- Life of Lykurgus -- Life of Numa -- Comparison of Numa with Lykurgus -- Life of Solon -- Life of Poplicola -- Comparison of Solon and Poplicola -- Life of Themistokles -- Life of Camillus -- Life of Perikles -- Life of Fabius Maximus -- Comparison of Perikles and Fabius Maximius -- Life of Alkibiades -- Life of Caius Marcius Coriolanus -- Comparison between Alkibiades and Coriolanus -- Life of Timoleon -- Life of Aemilius -- Comparison of Paulus Aemilius and Timoleon.
Wikipedia page about this book: https://en.wikipedia.org/wiki/Parallel_Lives
Release date is 2004-11-12
E-text prepared by Jonathan Ingram, Linda Cantoni, and the Project Gutenberg Online Distributed Proofreading Team, with special thanks to Thundergnat
Keywords: Greece -- Biography -- Early works to 1800; Rome -- Biography -- Early works to 1800